Training at maximal power in resisted sprinting: Optimal load determination methodology and pilot results in team sport athletes - Cross, M. R.; Lahti, J.; Brown, S. R.; Chedati, M.; Jimenez-Reyes, P.; Samozino, P.; Eriksrud, O.; Morin, J.-B. (PLOS ONE, 2018)
Aims In the current study we investigated the effects of resisted sprint training on sprinting performance and underlying mechanical parameters (force-velocity-power profile) based on two different training protocols: (i) loads that represented maximum power output (Lopt) and a 50% decrease in maximum unresisted sprinting velocity and (ii) lighter loads that represented a 10% decrease in maximum unresisted sprinting velocity, as drawn from previous research (L10). Methods Soccer [n = 15 male] and rugby [n = 21; 9 male and 12 female] club-level athletes were individually assessed for horizontal force-velocity and load-velocity profiles using a battery of resisted sprints, sled or robotic resistance respectively. Athletes then performed a 12-session resisted (10 × 20-m; and pre- post-profiling) sprint training intervention following the L10 or Lopt protocol. Results Both L10 and Lopt training protocols had minor effects on sprinting performance (average of -1.4 to -2.3% split-times respectively), and provided trivial, small and unclear changes in mechanical sprinting parameters. Unexpectedly, Lopt impacted velocity dominant variables to a greater degree than L10 (trivial benefit in maximum velocity; small increase in slope of the force-velocity relationship), while L10 improved force and power dominant metrics (trivial benefit in maximal power; small benefit in maximal effectiveness of ground force orientation). Conclusions Both resisted-sprint training protocols were likely to improve performance after a short training intervention in already sprint trained athletes. However, widely varied individualised results indicated that adaptations may be dependent on pre-training force-velocity characteristics.